A dosimetric comparison of proton and photon therapy in unresectable cancers of the head of pancreas. Issue 8 (22nd July 2014) - Thompson, Reid F.; Mayekar, Sonal U.; Zhai, Huifang; Both, Stefan; Apisarnthanarax, Smith; Metz, James M.; Plastaras, John P.; Ben‐Josef, Edgar
Abstract : Purpose: Uncontrolled local growth is the cause of death in ∼30% of patients with unresectable pancreatic cancers. The addition of standard‐dose radiotherapy to gemcitabine has been shown to confer a modest survival benefit in this population. Radiation dose escalation with three‐dimensional planning is not feasible, but high‐dose intensity‐modulated radiation therapy (IMRT) has been shown to improve local control. Still, dose‐escalation remains limited by gastrointestinal toxicity. In this study, the authors investigate the potential use of double scattering (DS) and pencil beam scanning (PBS) proton therapy in limiting dose to critical organs at risk. Methods: The authors compared DS, PBS, and IMRT plans in 13 patients with unresectable cancer of the pancreatic head, paying particular attention to duodenum, small intestine, stomach, liver, kidney, and cord constraints in addition to target volume coverage. All plans were calculated to 5500 cGy in 25 fractions with equivalent constraints and normalized to prescription dose. All statistics were by two‐tailed paired t‐test. Results: Both DS and PBS decreased stomach, duodenum, and small bowel dose in low‐dose regions compared to IMRT (p < 0.01). However, protons yielded increased doses in the mid to high dose regions (e.g., 23.6–53.8 and 34.9–52.4 Gy for duodenum using DS and PBS, respectively; p < 0.05). Protons also increased generalized equivalent uniform dose to duodenum and stomach, however these differences were small (<5% and 10%, respectively; p < 0.01). Doses to other organs‐at‐risk were within institutional constraints and placed no obvious limitations on treatment planning. Conclusions: Proton therapy does not appear to reduce OAR volumes receiving high dose. Protons are able to reduce the treated volume receiving low‐intermediate doses, however the clinical significance of this remains to be determined in future investigations.